Interferon Gamma Counteracts the Angiogenic Switch and Induces Vascular Permeability in Dextran Sulfate Sodium Colitis in Mice. Issue 10 (October 2015) - Haep, Lisa; Britzen-Laurent, Nathalie; Weber, Thomas G.; Naschberger, Elisabeth; Schaefer, Alexander; Kremmer, Elisabeth; Foersch, Sebastian; Vieth, Michael; Scheuer, Werner; Wirtz, Stefan; Waldner, Maximilian; Stürzl, Michael
Abstract : Background: Interferon (IFN)-γ is a central pathogenesis factor in inflammatory bowel disease (IBD) with pleiotropic effects on many different cell types. However, as yet, the immune modulatory functions of IFN-γ in IBD have been predominantly investigated. Based on previous studies showing that IFN-γ acts antiangiogenic in colorectal carcinoma, we investigated the effects of IFN-γ on the vascular system in IBD. Methods: Colon tissues of patients with IBD and dextran sulfate sodium–induced colitis in mice were subjected to immunohistochemistry, quantitative real-time polymerase chain reactions, and in situ hybridization to quantify cell activation, angiogenesis, and immune responses. Vascular structure and permeability in mice were analyzed by ultramicroscopy and in vivo confocal laser endomicroscopy. Results: We showed a significantly increased blood vessel density in IBD and dextran sulfate sodium colitis. In mice, this was associated with a disorganized blood vessel structure and profound vascular leakage. As compared with genes associated with angiogenesis, genes associated with inflammatory cell activation including IFN-γ were more strongly upregulated in colitis tissues. IFN-γ exerted direct effects on endothelial cells in IBD tissues in vivo, as indicated by the expression of IFN-γ–induced guanylate binding protein 1 (GBP-1). Neutralization of IFN-γ in the acute dextran sulfate sodium colitis model demonstrated that this cytokine exerts endogenous angiostatic activity in IBD and contributes to increased vascular permeability. Conclusions: The dissection of the pleiotropic activities of IFN-γ in IBD provides new insights to the pathological functions of this cytokine and may be of high relevance for the optimization of combination therapy approaches. Abstract : Article first published online 9 July 2015.Supplemental Digital Content is Available in the Text.